Bianchi Type V Universe Filled with Combination of Perfect Fluid and Scalar Field Coupled with Electromagnetic Fields in f(R,T) Theory of Gravity. (Global Journal of Science Frontier Research, 2017)
In (, ) theory of gravity, we have studied the combination of perfect fluid and scalar field interacting with electromagnetic fields in Bianchi type V space-time, by considering the general cases (, ) = () + (), (, ) = () () and () theory and its particular cases (, ) = + , (, ) = and () = . It is observed that, even though the line element of space-time are distinct, the convergent and isotropic solution of metric functions can be evolved in each case along with the components of vector potential, corresponding to suitable integrable function in particular cases.
Keywords: theory of gravity; space-time; Bianchi type; vector potential